Shear-induced diffusion and dynamic heterogeneities in dense granular flows - Saitoh, Kuniyasu; Kawasaki, Takeshi (Frontiers in Physics, 2022)
We study two-dimensional dense granular flows by molecular dynamics simulations. We quantify shear-induced diffusion of granular particles by the transverse component of particle displacements. In long time scales, the transverse displacements are described as normal diffusion and obey Gaussian distributions, where time correlations of particle velocities entirely vanish. In short time scales, the transverse displacements are strongly non-Gaussian if the system is dense and sheared quasistatically though memory effects on the particle velocities are further suppressed. We also analyze spatio-temporal structures of the transverse displacements by self-intermediate scattering functions and dynamic susceptibilities. We find that the relation between the maximum intensity and characteristic time scale for dynamic heterogeneities is dependent on the models of contact damping (which exhibit different rheological properties such as the Newtonian fluids' behavior and shear thickening). In addition, the diffusion coefficient over the shear rate is linear (sub-linear) in the maximum of dynamic susceptibility if the damping force is not restricted (restricted) to the normal direction between the particles in contact.